The Effect of Cerium Doping on LiTaO3 Thin Film on Band Gap Energy - Ismangil, Agus; Subiyanto, Subiyanto; Sudradjat, Sudradjat; Prakoso, Wahyu Gendam; Saepulrohman, Asep (International Journal of Electronics and Communications Systems, 2021)
Lithium tantalite LiTaO3 was grown on a Si Type-P (100) substrate by chemical solution deposition and spin coating methods at a speed of 3000 rpm for 30 seconds with an annealing temperature of 800 ° C, 900 ° C. This study aims to determine the effect of temperature variations on the band gap energy. The results show that the energy band gap value of the thin film has a significant impact on the interpretation of annealing temperature. It can be seen that a high energy band gap peak occurs at an annealing temperature of 900 ° C and a time of 15 hours of the energy band gap of 1,49 eV. This shows the effect of temperature variations on the energy band gap to move from the valence band to the conduction band, which will produce current.